STUDI TERHADAP ASPEK KEUNGGULAN KITAB SAHIH MUSLIM TERHADAP SHAHIH BUKHARI - Abdul Wahid Arsyad (Islam Futura, 2018)
The book of Sahih Muslim is the best book of hadith after the book of Sahih Bukhari. Even some scholars of hadith even claim that the Shahih Muslim is higher in value than the book of Sahih Muslim. In certain respects the scholars generally acknowledge the superiority of the book of Sahih Muslim, although the accumulative book of Shahih Bukhari remains the best book. In the reality of Islamic society, some people even think that Bukhari and Muslim are one unity, in the sense of being one person and one inseparable work. too much different, even in certain areas even having an inverse value. This paper seeks to explain the aspects of excellence owned by Muslim shahih books, such as in the methodology aspects of writing the book, the repetition of hadith and the accuracy of the placement of hadith and the determination of the theme of hadith.